2023
DOI: 10.1101/2023.05.23.541792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous pathology in tauopathy mice progresses via brain networks

Denise M.O. Ramirez,
Jennifer D. Whitesell,
Nikhil Bhagwat
et al.

Abstract: Neurodegenerative tauopathies are hypothesized to propagate via brain networks. This is uncertain because we have lacked precise network resolution of pathology. We therefore developed whole-brain staining methods with anti-p-tau nanobodies and imaged in 3D PS19 tauopathy mice, which have pan-neuronal expression of full-length human tau containing the P301S mutation. We analyzed patterns of p-tau deposition across established brain networks at multiple ages, testing the relationship between structural connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our study showed significant DCS differences between the WT and Tau mouse groups in regions including the cortical amygdala, entorhinal cortex, and piriform cortical areas, that are known to be severely affected by tau pathology (Hurtado et al, 2010;Ramirez et al, 2023). Previous studies have largely reported increased paramagnetic susceptibility associated with tau pathology, in both human brain and animal models.…”
Section: Discussionmentioning
confidence: 54%
“…Our study showed significant DCS differences between the WT and Tau mouse groups in regions including the cortical amygdala, entorhinal cortex, and piriform cortical areas, that are known to be severely affected by tau pathology (Hurtado et al, 2010;Ramirez et al, 2023). Previous studies have largely reported increased paramagnetic susceptibility associated with tau pathology, in both human brain and animal models.…”
Section: Discussionmentioning
confidence: 54%
“…While some reported tau propagate in a similar manner regardless of the disease-specific inoculum [ 15 , 29 , 45 , 48 , 71 ], others showed different patterns of propagation [ 19 , 161 ]. In a nutshell, both anterograde and retrograde propagation of tau in both transgenic and WT models are related more to the strength of the connectivity of neuronal networks between the inoculation region and another brain region, rather than to the proximity of the brain region to the injection site [ 127 ].…”
Section: Resultsmentioning
confidence: 99%